Author Correction: Comparative transcriptome analysis of Sclerotinia sclerotiorum revealed its response mechanisms to the biological control agent, Bacillus amyloliquefaciens - Xiaoxiang Yang (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.